Existential Distress in Cancer Patients: A Concept Analysis. Issue 2 (March 2022) - Chen, Weiling; Chen, Ying; Xiao, Huimin
Abstract : Background: Existential distress is a widely used concept used in describing cancer patients. However, this concept is vague and has failed to achieve a consensus. The lack of a recognized conceptual framework could hinder future research on existential distress. Objective: The aim of this study was to clarify and analyze the concept of existential distress in cancer patients. Methods: The Walker and Avant concept analysis approach was applied. Results: For cancer patients, the concept of existential distress included 5 core attributes: ( a ) lack of meaning; ( b ) loss of autonomy; ( c ) loss of dignity; ( d ) hopelessness; and ( e ) death anxiety. Existential distress is a key factor causing poor quality of life, a poor emotional state, demoralization, and even suicide. It is often underpinned by uncontrolled physical pain, serious psychological morbidity, and a perceived sense of being a burden on others. Conclusion: The concept analysis provides a theoretical framework for healthcare providers to better understand existential distress in cancer patients, to improve patient well-being. Implications for Practice: On the basis of the antecedents of this concept, cancer patients experiencing uncontrolled physical pain, severe psychological morbidity, and a perceived sense of being a burden on others are at a high risk of existential distress. These factors should be eliminated in a timely manner to prevent cancer patients from being caught in a state of existential distress. The 5 defining attributes and empirical referents of this concept could be used to develop tools to screen for existential distress in cancer patients and distinguish it from similar concepts.